Ljudske plesne pesmi na Slovenskem - Ramovš, Mirko (Traditiones (Ljubljana), 1999)
In his article the author defines Slovene folk dance songs, gives a survey of them, and suggests their classification
Keywords: slovenski ljudski plesi; plesi; Ethnopoetics; ljudske pesmi; ljudski plesi; etnomuzikologija